Ryegrass organelle genomes : phylogenomics and sequence evaluation - Diekmann, Kerstin (Trinity College (Dublin, Ireland). Department of Botany, 2010)
Perennial ryegrass (Lolium perenne L.) is the most important forage grass of temperate regions of the world. The main objective in breeding perennial ryegrass cultivars is to increase its biomass. Chloroplasts and mitochondria are two organelles of the plant cell that are actively involved in biomass production. Chloroplasts derive from cyanobacteria and are the location of photosynthesis in plant cells. Mitochondria derive from α-proteobacteria and are involved in cell respiration. Due to their evolutionary history both organelles still contain their own genome which is in general maternally inherited. The interest in chloroplast genome sequences increased in recent years because they offer a useful option for plant genetic engineering. The risk of transgene escape via pollen flow is reduced while the expression of the transgene due to the high number of chloroplast genome copies is increased (in comparison to nuclear genome transformation). Mitochondrial genomes are of special interest because they are involved in cytoplasmic male sterility. Cytoplasmic male sterility is a very important trait in plant breeding programmes because it enables the cost efficient production of hybrid seed. Additionally, both organelle genomes can be used for molecular evolution or phylogenetic studies, as well as for population genetic approaches. Therefore the major aim of this thesis was to sequence the entire chloroplast and mitochondrial genomes of L. perenne to provide sequence information for chloroplast genetic engineering approaches, insights into the mitochondrial genome of a male fertile L. perenne cultivar and to gather knowledge about sequence variation in both genomes that can be used to design new markers for phylogenetic and population genetic studies.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.